2021
DOI: 10.1029/2020ja028360
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Signatures of Secondary Waves From Quasi‐6‐Day Wave and Tide Interactions

Abstract: The state of the ionosphere significantly changes from day to day. The ionospheric weather is controlled not only by forcing from above (e.g., solar radiation and energy deposition from the magnetosphere) but also by forcing from below, through upward-propagating waves, such as planetary waves, tides, and gravity waves (e.g., Liu, 2016). Sudden stratospheric warmings (SSWs) are extreme meteorological events that disturb the whole atmosphere (e.g., Chau et al., 2012;Pedatella et al., 2018) and thus provide oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
4
3
0
Order By: Relevance
“…Figure 2 and Figure S2 in Supporting Informtion indicate that the Q6DWs in the upper MLT observed in 2019 are the most prominent from 2005 to 2020 in both hemispheres. These observations are highly consistent with the results reported in previous studies (Yamazaki, 2018; Yamazaki et al., 2020; Yamazaki & Miyoshi, 2021), which indicate the Q6DWs at 0.001 hPa is the strongest in Aura/MLS observations at mid‐latitudes in both hemispheres since August 2004. Thus, the enhancement of Q6DWs in both hemispheres in the autumn of 2019 cannot be fully explained by their climatological activities.…”
Section: Observationssupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 2 and Figure S2 in Supporting Informtion indicate that the Q6DWs in the upper MLT observed in 2019 are the most prominent from 2005 to 2020 in both hemispheres. These observations are highly consistent with the results reported in previous studies (Yamazaki, 2018; Yamazaki et al., 2020; Yamazaki & Miyoshi, 2021), which indicate the Q6DWs at 0.001 hPa is the strongest in Aura/MLS observations at mid‐latitudes in both hemispheres since August 2004. Thus, the enhancement of Q6DWs in both hemispheres in the autumn of 2019 cannot be fully explained by their climatological activities.…”
Section: Observationssupporting
confidence: 93%
“…Based on the long-term measurement of the Aura/MLS geopotential heights from 2005 to 2020, a significance test is performed on the monthly mean Q6DWs in September. As shown in Figure 2 results reported in previous studies (Yamazaki, 2018;Yamazaki et al, 2020;Yamazaki & Miyoshi, 2021), which indicate the Q6DWs at 0.001 hPa is the strongest in Aura/MLS observations at mid-latitudes in both hemispheres since August 2004. Thus, the enhancement of Q6DWs in both hemispheres in the autumn of 2019 cannot be fully explained by their climatological activities.…”
Section: Observationssupporting
confidence: 61%
“…Specifically, the PC#1 is likely linked to plasma transport by in-situ neutral winds that are modulated by upward propagating tides; those relevant tidal components interact with the Q6DW at lower altitudes. A similar coupling paradigm has been demonstrated (Gan et al, 2017(Gan et al, , 2020aForbes et al, 2018;Miyoshi and Yamazaki, 2020;Yamazaki and Miyoshi, 2021) in prior studies. A recent study by Forbes et al (2020) also suggested that the Q6DWs can be generated in the thermosphere via a two-step nonlinear wave-wave interaction.…”
Section: Resultssupporting
confidence: 67%
“…Planetary‐scale oscillation with periods of 4–7 days is known as the quasi‐5‐day oscillation (Q5DO), which plays a significant role in the disturbances of stratospheric temperatures, mesospheric winds, and ionospheric total electron contents (e.g., Gan et al., 2015; Gong et al., 2018; Huang et al., 2017; Yamazaki, 2018; Yamazaki & Miyoshi, 2021). Previous studies mainly investigated the westward propagating Q5DO at central periods of 5‐day, 6‐day, and 6.5‐day with a zonal wavenumber of 1 (W1), which were discussed as “quasi‐5‐day waves (Q5DW)”, “quasi‐6‐day waves (Q6DW)” and “6.5‐day waves (6.5DW)”, respectively (Belova et al., 2008; Day et al., 2012; Iimura et al, 2015; Lieberman et al., 2003; Merkel et al., 2003; Merzlyakov et al., 2013; Pancheva et al., 2018; Takahashi et al., 2006; Wu et al., 1994).…”
Section: Introductionmentioning
confidence: 99%